Tax: Tax Policy, State Revenue, and Its Impact on Society - Buono, Leo (Sultan Agung Notary Law Review, 2025)
Tax policy plays an important role in economic development, especially in developing countries. Tax is the main source of income for the government which is used to finance various development programs and projects, such as infrastructure, education, and health in a country. Its function is not only as a source of state income, but also as a supporter of various development programs and public welfare. In this article, we will explore more deeply the tax collection process, who is affected by it, and how the role of taxes in supporting development and public welfare. Taxes, which are collected and administered by tax authorities such as the Directorate General of Taxes (DGT) in our country, have a crucial role in raising funds to support government activities. Through effective tax policies, the government can allocate resources more efficiently and support economic growth. The purpose of taxation cannot be separated from the purpose of the government. Therefore, the purpose of taxation must be in accordance with the purpose of the government, namely under the purpose of the government. The concept of taxation and the concept of government are rooted in the concept of society. The purpose of this society is the state and its ideas. the purpose of taxation cannot be separated from its main purpose. in addition to being used for development, taxes collected from the community should also be used for the needs and welfare of the community itself. This study aims to analyze the impact of tax policy on economic growth in developing countries. By understanding how tax policy affects various aspects of the economy, this study is expected to provide relevant recommendations for policy makers in designing more effective and sustainable tax policies.